“Гўрўғли” туркум ДОСТОНЛАРИДА Аваз образи - Мирзаев, Ж.Н. (SCIENCE and SOCIETY, 2020)
The artistic image appears in each text in a unique way. In different versions and variations of dastans that have survived to the present day, a single image is described in different ways. This, of course, reflects not only the epic tradition of upbringing, but also mythological ideas, customs, values and concepts that belong only to this nation. Avaz is one of the main heroes in the dastan «Gorogly» after Gorogly. The Uzbek and Tajik versions of the dastan we analyzed and showed similarities as well as different features of the image of Avaz. In our article, we have tried to make a comparative study of the image of Avaz in the Uzbek and Tajik versions of dastan "Gorogly".